SAFETY ANALYSIS OF EARTHFILL DAMS ON CONSTRUCTION OF SEI GONG ESTUARY DAM - Kumala Wibihestusri, Daru
Sei Gong Dam is an estuary dam located in Batam City, Riau Islands Province. Nowadays, the construction of Sei Gong Dam was finished thus the filling of a reservoir will be carried out. Hence the first filling of a reservoir is the critical phase of earth fill dam so that the analysis of dam safety design necessary to be monitored toward safety of hydraulics aspects, seepage and structure boundary before the filling performed. Sei Gong Dam is a dam with low height and little risk that used Q1000 as the flood design and the minimum spillway capacity is 15% of peak discharge QPMF. In this research, the analysis of flooding design (HSS SCS) based on the rainfall data from 1999 to 2018 was achieved 613,81 m3/s of QPMF and 455,02 m3/s of Q1000.. From the analysis, the spillway capacity of 26,8% peak discharge QPMF was achieved and the freeboard Q1000 of 1,08 m < the minimum freeboard (H2) of 1,88 m. On the analysis of seepage with SEEP/W, the seepage discharge in center line of dam was 6,851x10-7 m3/s and the safety factor toward piping of 7,2 > the minimum safety factor of 4. On the analysis of slope stability, the analysis was done with several methods and conditions with the earthquake coefficients OBE and MDE, 100 years and 1000 years respectively, from the earthquake map of 2010 and 2017. The analysis was calculated using SLOPE/W, the least safety factor was 1,823, in an upstream slope in condition of rapid drawdown from the flood design elevation to the elevation of dead storage (K=0,051), used Janbu’s Method. This result had met the requirement of minimum safety factor. Accordingly, Sei Gong Dam was satisfied toward the safety of seepage and structure. However, there is a risk of runoff during floods in the dam. To reduce this risk, the parapets need to be installed as high as 1 m so that the peak elevation of the dam become +13,00 m.